Selectivity in search strategies for innovation: from incremental to radical, from manufacturing to services - Christian Köhler; Wolfgang Sofka; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The shift towards more open and interconnected innovation activities has been a major topic of recent academic and practitioner discussions. Firms have to connect their in-house R&D activities with external partners, such as leading customers or universities, to increase the effectiveness of their innovation activities. Hence, management needs to define search strategies for valuable knowledge in its environment. In this paper we argue that search strategies have to reflect the heterogeneity of various knowledge sources with regard to the knowledge they can provide and how these sources can be activated. We hypothesize that search strategies driven by science, suppliers and the product market will contribute differently to innovation success with radically new versus incrementally refined products. We suggest that innovation in service sectors is fundamentally different in nature which influences the performance of different search strategies. We test these hypotheses for a sample of more than 5,000 firms from five European countries. The results support our hypotheses and highlight the potentials and shortcomings of different search strategies.
Keywords: L60; O32; 330; Search strategies; service innovation; radical versus incremental innovation; Innovation; Wissenstransfer; Informationsverhalten; Suchtheorie; Industrielle Forschung; Dienstleistungssektor; EU-Staaten